(The Modern Activities for Internal Revision and Its Roles on Performance and Effectiveness to Electronic Government(Study on Tax Department in Khartoum State - Abaker, Mohammed Ishag Abdalla; Osman, Mohyeeeldin Mohmed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2019)
This research investigates the relationship between the roles of modern activities for internal revision presented in consultancy services, confirmation services, risk management and effectiveness of performing electronic government through governmental units. The researchers used questionnaire form for collecting field data from internal auditors and inspectors of tax department in Khartoum State. The research found that there is direct correlation between the role of modern activities for internal revision and effectiveness for performing electronic government in tax department. This research recommends in increasing the units of government by the roles of modern activities for internal revision to ensure greater effectiveness on performing the electronic government.